The Impression Management Strategy of the Candidates of Governor-Vice Governor of DKI Jakarta on Social Media - Endah Murwani (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2018)
The use of social media is not only important but also strategic means of political communication in the Regional Leader Election (Pilkada) of DKI Jakarta and is interesting to be examined, particularly from the view of Erving Goffman’s Self Presentation—Impression Management Theory. This research aims at illustrating the impression management strategy of the Governor-Vice Governor candidates for DKI Jakarta, namely Ahok-Djarot and Anies-Sandi, through social media. We apply qualitative analyses to the Instagram feeds and Twitter timelines of the two duos from October 2016 to April 2017. The result shows that the candidates attempt to present themselves by projecting the images they want. Ahok-Djarot applies three strategies: 1) credibility strategy, presenting competency, achievements, performance during their time in the office of DKI Jakarta as well as their characters—enthusiastic, firm, and focus to positive matters; (2) politeness strategy, by illustrating themselves as two concerned, friendly, and humorist persons; (3) influencing strategy, to spread influence; (4) self-deprecating strategy to draw sympathy from the citizens about the problems faced by Ahok. On the other hand, Anies-Sandi utilize these three strategies: 1) affinity seeking and politeness strategy to make them acknowledged and liked by the netizens; 2) image confirming strategy to make the netizens have the image of who Anies-Sandi are; and (3) credibility strategy by showcasing their achievements prior to being the Governor-Vice Governor of DKI Jakarta candidates.